KETIDAKADILAN GENDER TERHADAP PEREMPUAN DALAM NOVEL PADUSI KARYA KA’BATI - Daratullaila Nasri (Balai Bahasa Provinsi Riau, 2016)
This thesis is a feminism criticism to a literature created by women. Related to the feminism criticism, the thesis is in the purpose to discover any kind of gender injustices to women in literatures. The injustices happened to women and written by women in Padusi novel are obviously different from literatures written by men. In order to discover the injustices, descriptive analysis method was used for this thesis. The injustices discovered in Padusi novel are: women subordination, negative stereotype to women, and the burden of double job. Gender injustice caused by patriarchy system in society. This patriarchy system is not only being applied by men only, but also by women. Matrilineal systemcannot prevent the injustice. If literature (novel) is considered as a reflection of society, then Padusi novel which taking Minangkabau custom as its background that profess matrilineal system has reflected it.